Bystander preference for naloxone products: a field experiment - Katherine R. Marks; Douglas R. Oyler; Justin C. Strickland; Jody Jaggers; Monica F. Roberts; Dustin K. Miracle; Chase Barnes; Feitong Lei; Amanda Smith; Eric Mackin; Martika C. Martin; Patricia R. Freeman (BMC, 2023)
Abstract Background Bystander administration of naloxone is a critical strategy to mitigate opioid overdose mortality. To ensure bystanders' willingness to carry and administer naloxone in response to a suspected overdose, it is critical to select products for community distribution with the highest likelihood of being utilized. This study examines bystanders' preference for and willingness to administer three naloxone products approved by the FDA for bystander use and identify product features driving preference. Methods The population was a convenience sample of individuals who attended the Kentucky State Fair, August 18-28, 2022, in Louisville, Kentucky. Participants (n = 503) watched a standardized overdose education and naloxone training video, rated their willingness to administer each of three products (i.e., higher-dose nasal spray, lower-dose nasal spray, intramuscular injection), selected a product to take home, and rated factors affecting choice. Results After training, 44.4% chose the higher-dose nasal spray, 30.1% chose the intramuscular injection, and 25.5% chose the lower-dose nasal spray. Factors most influencing choice on a 10-point Likert scale were ease of use (9 [7-10]), naloxone dose (8 [5-10]), and product familiarity (5 [5-9]). Conclusions Bystanders expressed high willingness to administer all studied formulations of naloxone products. Product choice preference varied as a function of product features. As the number and variety of available products continue to increase, continuous evaluation of formulation acceptability, in addition to including individuals with lived experience who are receiving and administering overdose reversal agents, is critical to support adoption and save lives.